PENGARUH PENGGUNAAN ENDORSER BAND VIERRA PADA IKLAN HONDA SCOOPY DI TELEVISI TERHADAP TERBENTUKNYA BRAND IMAGE - Adithya S, Ardi (Universitas Prof. Dr. Moestopo (Beragama), 2012)
The research was motivated by many marketers and advertising making use of celebrity endorsers in particular to introduce and promote a product or service. The use of celebrities as endorsers for a commercial product or service expected to impart increased awareness and establish a positive impression in the minds of consumers, and ultimately creating a follow-purchase. Based on the background of the problem, the formulation of the problem in this research is how much influence the use of endorsers in advertisements Band Vierra Honda Scoopy the formation of brand image among adolescent RW 010 Housing II Karawaci Tangerang?. While the purpose of this study was to determine the response teenagers RW 010 Housing II Karawaci Tangerang Vierra as an endorser of the influence on the formation of an ad Honda Scoopy television brand image, know the brand image of Honda Scoopy. As the cornerstone think this study used the theory Stimulus-Organism-Response. This theory is supported by the model need VISCAP. In addition to describing the process of the formation of brand image (brand image), the author uses the theory of Hierarchy Effects Off. The method used is explanatory. Decision-sampling technique using simple random sampling proportionate sample. Data was collected by distributing questionnaires to the respondents technique. Then the data is collected and interpreted quantitatively analyzed to obtain an overview of the observed variables. After that hypothesis testing using Pearson product moment technique. Based on research and analysis of data that Honda Scoopy ads on television quite good.